2008
DOI: 10.7202/016954ar
|View full text |Cite
|
Sign up to set email alerts
|

Activity System Model, Perceived Self-Efficacy, and Newcomer Integration Behaviour

Abstract: The research presented here contributes to the current debate on the effects of perceived self-efficacy (PSE). The study, undertaken with 157 schoolteachers who had just started their first teaching position, examined the moderating role of PSE on the effects of mismatches between expectations and actual work conditions on newcomer integration behaviour. Based on the theoretical model of multiple socialization, the results suggest that: 1) the degree of exchanges that subjects establish between different areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In our study, we found that the simple act of playing video games may actually provide its own mastery experience, allowing students to feel more comfortable and proficient with computers via this primarily entertainment medium. Furthermore, our findings also indicate that self-efficacy beliefs that are internally located within one particular sphere of activity (i.e., leisure-based video gameplay) may bleed into other tangentially related spheres of activity (i.e., occupation-related STEM attitudes; Almudever et al, 2007;Bandura, 1997Bandura, , 1999Bandura, , 2006. This finding is in line with previous findings indicating the viability of gaming as a means to teach technology-related skills (Admiraal, 2015;Ting, 2010).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In our study, we found that the simple act of playing video games may actually provide its own mastery experience, allowing students to feel more comfortable and proficient with computers via this primarily entertainment medium. Furthermore, our findings also indicate that self-efficacy beliefs that are internally located within one particular sphere of activity (i.e., leisure-based video gameplay) may bleed into other tangentially related spheres of activity (i.e., occupation-related STEM attitudes; Almudever et al, 2007;Bandura, 1997Bandura, , 1999Bandura, , 2006. This finding is in line with previous findings indicating the viability of gaming as a means to teach technology-related skills (Admiraal, 2015;Ting, 2010).…”
Section: Discussionmentioning
confidence: 56%
“…Spheres of activity constitute domain-specific conglomerations of subskills surrounding specific domains of functionality (Bandura, 2006). For example, self-efficacy beliefs may be internally categorized within occupational, personal, and leisure domains that share particular skill sets (Almudever, Croity-Belz, & Hajjar, 2007). Self-efficacy is particularly important because internal beliefs may influence how an individual thinks, feels, and behaves (Bandura, 1994).…”
Section: Theoretical Framework: An Overview Of Sctmentioning
confidence: 99%